Label-free determination of the number of biomolecules attached to cells by measurement of the cell's electrophoretic mobility in a microchannel. - Atsushi Aki (Public Library of Science (PLoS), 2010)
We developed a label-free method for a determination of the number of biomolecules attached to individual cells by measuring the electrophoretic mobility of the cells in a microchannel. The surface of a biological cell, which is dispersed in aqueous solution, is normally electrically charged and the charge quantity at the cell's surface is slightly changed once antibody molecules are attached to the cell, based on which we detect the attachment of antibody molecules to the surface of individual red blood cells by electrophoretic mobility measurement. We also analyzed the number of antibody molecules attached to the cell's surface using a flow cytometer. We found that there is a clear correlation between the number of antibody molecules attached to the individual cells and the electrophoretic mobility of the cells. The present technique may well be utilized not only in the field of cell biology but also in the medical and pharmaceutical industries.